ANALISIS PERUBAHAN TUTUPAN LAHAN DAS ASAM–ASAM KECAMATAN JORONG KABUPATEN TANAH LAUT PERIODE 2000 SAMPAI 2017 - Dika Aditya Nugraha; Eko Rini Indrayatie; Suyanto Suyanto (Universitas Lambung Mangkurat, 2020)
This study aims to analyze the shape and rate of land cover change for the period 2000 to 2017, the method used in this study is image interpretation and data analysis. There are 15 classifications namely water body, shrub, swamp shrub, secondary mangrove forest, primary dryland forest, secondary dryland forest, plantations, mixed dryland agriculture, plantations, settlements, dry land agriculture, swamps, open land, open land, mining and pond. There is an increase in the type of land cover in 2017. The most dominant land cover in 2000 in the Asam-Asam watershed was 39399 ha of forest with a percentage of 78.66% while based on land cover data of Landsat 7 in 2017 the forest area was reduced to 16755, 6 Ha with a percentage of 33.45%. The function of forest area in the APL area is the biggest change, namely secondary dryland forest to dryland agriculture with an area of 2118.8 Ha, for the function of forest area in the HL region the largest is secondary dryland forest into shrubs with an area of 507.4 Ha, at HP area has the biggest change, namely plantation forest to plantation with an area of 5036.2 Ha, the function of HPK area is the biggest change in secondary dryland forest into shrubs with an area of 238.2 Ha, the next area Riam Kanan is primary dryland forest into secondary dryland forest with an area of 3545.7 ha and in the area of the Pelaihari TWA forest function the largest is secondary swamp forest into swampland with an area of 217.9 ha.